2021
DOI: 10.1162/netn_a_00183
|View full text |Cite
|
Sign up to set email alerts
|

Gradients of connectivity as graph Fourier bases of brain activity

Abstract: The application of graph theory to model the complex structure and function of the brain has shed new light on its organization, prompting the emergence of network neuroscience. Despite the tremendous progress that has been achieved in this field, still relatively few methods exploit the topology of brain networks to analyze brain activity. Recent attempts in this direction have leveraged on the one hand graph spectral analysis (to decompose brain connectivity into eigenmodes or gradients) and on the other on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 94 publications
0
30
0
Order By: Relevance
“…Recall that formally, the progression from low- to high-frequency connectome harmonics reflects increasing decoupling of functional brain activity from the underlying structural connectivity 53 , 76 , 77 (Fig. 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recall that formally, the progression from low- to high-frequency connectome harmonics reflects increasing decoupling of functional brain activity from the underlying structural connectivity 53 , 76 , 77 (Fig. 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to the Fourier transform for the time domain, applications include filtering and spectral analysis 52 54 . The approach has found increasing application in neuroscience, albeit with a wide variety of names and mathematical operationalisations 53 . Graph Signal Processing is also mathematically and conceptually related to Graph Spectral Theory, which is primarily used for dimensionality reduction of graph-based data, including the well-known principal gradient of functional connectivity introduced by Margulies 55 , and subsequent applications to structural, microstructural, and other forms of connectivity 56 , 57 ; being nonlinear, this graph-based approach can provide a superior characterisation than what is obtained from linear approaches such as Independent Components Analysis and Principal Components Analysis 53 , 58 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We then employed diffusion map embedding, a nonlinear manifold learning technique based on the graph Laplacian 140, 254 , to obtain a low dimensional representation of the joint drug- and disorder-susceptibility. A single parameter α controls the influence of the sampling density on the manifold (α = 0, maximal influence; α = 1, no influence).…”
Section: Methodsmentioning
confidence: 99%
“…However it is often possible to use other imaging techniques, as well as previous studies, to build a graph that models dependencies between brain areas [23]. Several prior studies have shown the potential of using transfer learning [24,25] or GSP to analyze fMRI data [26,27], resulting in better classification of signals using subsets of the obtained features [28,29,30].…”
Section: Related Workmentioning
confidence: 99%